2015
DOI: 10.1155/2015/287640
|View full text |Cite
|
Sign up to set email alerts
|

Activins and Follistatin in Chronic Hepatitis C and Its Treatment with Pegylated‐Interferon‐α Based Therapy

Abstract: Pegylated-interferon-α based therapy for the treatment of chronic hepatitis C (CHC) is considered suboptimal as not all patients respond to the treatment and it is associated with several side effects that could lead to dose reduction and/or termination of therapy. The currently used markers to monitor the response to treatment are based on viral kinetics and their performance in the prediction of treatment outcome is moderate and does not combine accuracy and their values have several limitations. Hence, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 162 publications
(308 reference statements)
0
8
0
Order By: Relevance
“…Activins play crucial roles in many cellular homeostatic functions including cell proliferation and differentiation, wound repair and regulation of immune responses [10]. Pathological increase in activin βA-subunit protein and mRNA has been observed in malignant tissues obtained from patients with CRC and the expression was stage-dependent [19–21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activins play crucial roles in many cellular homeostatic functions including cell proliferation and differentiation, wound repair and regulation of immune responses [10]. Pathological increase in activin βA-subunit protein and mRNA has been observed in malignant tissues obtained from patients with CRC and the expression was stage-dependent [19–21].…”
Section: Discussionmentioning
confidence: 99%
“…In this regards, gene deletion of activin βA- and βB-subunits resulted in completely different phenotypes and the insertion of INHBB in INHBA −/− mice partially restored the lost functions [44, 45]. Additionally, there is a tremendous gap in our knowledge and understanding of the potential physiological and pathological roles of the other activin isoforms (B & AB) in the different cells and tissues since the majority of studies were mainly conducted on activin-A only [10]. Nevertheless, a recent study has shown that patients with breast cancer and were positive for epidermal growth factor receptor 2/neu, which is a marker of carcinogenesis, had significantly lower serum concentrations of activin-AB [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activin A and follistatin are produced by normal and abnormal hepatocytes and help regulate hepatocyte regeneration in the healthy liver. Pathological increase of both activin and follistatin in hepatocyte is shown with several liver diseases including fibrosis, cirrhosis, and hepatocellular carcinoma (16). Activin A has shown an increase in serum from older women (43-47 years old) relative to younger women (19-38 years old) (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…High activin to follistatin ratio therefore favors a proinflammatory fibrotic state. 3 Activin A and its antagonist follistatin have been recognized as regulatory factors in a number of acute and chronic diseases including cirrhosis, 6 rheumatoid arthritis, 7 chronic kidney disease, 8 cachexia, 9 and several lung diseases. 10-14 …”
mentioning
confidence: 99%